THE MEANING OF ASPECTUALITY IN TARI SURU - Pristami Kusya Pristami Kusya; Arza Aibonotika Arza Aibonotika; Hana Nimashita Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research describes about the use of the meaning of aspectuality in tari suru. The purpose of this research is to know and inform about the meaning of aspectuality in tari suru. Aspectuality is associated with the element of time. Aspectuality only reffering to time from the situation ( beginning, the initial progress or at the end of a situation that is nondeictic). In the Japanese language as well, aspectuality as a function semantic category refers to situations when the element internal/external may be disclosed through the disclosure of internal variability iin the morphology and functional context in syntax level. Descriptive method is the method that applied in this research. The writer used the data from Japanese books, there are N3 ‘Nihongo noryoukushiken bunpou mondai taisaku’ by Shigeno Mie :2005, Japanese a Compreherensive Grammar by Kaiser, Stefan. 2001, and A Dictionary of Basic Japanese Grammar by Seiichi Makino & Michio Tsutsui. 1994. Keywords: Aspectuality, the meaning of aspectuality, tari suru